Influence of the nucleation surface on the growth of epitaxial Al2O3 thermal CVD films deposited on cemented carbides. (April 2022) - Zhu, Maoxiang; Achache, Sofiane; Emo, Mélanie; Borroto Ramírez, Alejandro; Pierson, Jean-François; Sanchette, Frédéric
Graphical abstract: Highlights: The nucleation of α- and κ-Al2 O3 can be controlled with specific nucleation treatments. α-Al2 O3 is the preferred alumina phase to be deposited without any nucleation treatment. α-Al2 O3 is grown epitaxially on rutile (TiO2 ), with ( 1 ¯ 20 ) α - A l 2 O 3 / / ( 10 1 ¯ ) r u t i l e, ( 003 ) α - A l 2 O 3 / / ( 010 ) r u t i l e and [ 210 ] α - A l 2 O 3 / / [ 101 ] r u t i l e . κ-Al2 O3 is grown epitaxially on Ti(C, N), with ( 100 ) κ - A l 2 O 3 / / ( 1 ¯ 1 ¯ 1 ) T i ( C, N ), ( 0 1 ¯ 3 ) κ - A l 2 O 3 / / ( 2 ¯ 20 ) T i ( C, N ) and [ 031 ] κ - A l 2 O 3 / / [ 112 ] T i ( C, N ) . Abstract: This work aims at understanding the nucleation and growth of alumina films grown on Ti(C, N)-based layers using an industrial-scale CVD system. Firstly, Al2 O3 layer was deposited on Ti(C, N)-based layers without any nucleation treatment, pure α-Al2 O3 is obtained, whereas no orientation relationship at the Ti(C, N)/α-Al2 O3 layers interface can be observed. Secondly, Al2 O3 layer was deposited on the bonding layer consisting of rutile TiO2, which is obtained by oxidizing the uppermost part of Ti(C, N)-based layers. Herein, α-Al2 O3 single-phased layer is obtained, and the epitaxial growth of α-Al2 O3 on rutile is observed. The orientation relationships can be found as: ( 1 ¯ 20 ) α - A l 2 O 3 / / ( 10 1 ¯ ) r u t i l e, ( 003 ) α - A l 2 O 3 / / ( 010 ) r u t i l e and [ 210 ] α - A l 2 O 3 / / [ 101 ] r u t i l e . Finally, Al2 O3 layer was deposited on the bonding layer, produced from a TiCl4 -H2 -N2 -CH4 -CO-AlCl3 gas mixture. Regarding this intermediate layer, despite additions of CO and AlCl3, no evidence for oxide phases, e.g. TiO2 and Al2 O3 can be found, while Ti(C, N) needle-shaped grains develop. In this case, κ-Al2 O3 is epitaxially grown on Ti(C, N), with the orientation relationships found as:. ( 0 1 ¯ 3 ) κ - A l 2 O 3 / / ( 2 ¯ 20 ) T i ( C, N ), ( 100 ) κ - A l 2 O 3 / / ( 1 ¯ 1 ¯ 1 ) T i ( C, N ) and [ 031 ] κ - A l 2 O 3 / / [ 112 ] T i ( C, N ) . Since processing parameters for the alumina depositions were always the same, it is revealed that the nucleation of α-Al2 O3 and κ-Al2 O3 can be accurately controlled with deposition of specific bonding layers.